Unique role for dentate gyrus microglia in neuroblast survival and in VEGF‐induced activation. Issue 4 (19th November 2018) - Kreisel, Tirzah; Wolf, Brachi; Keshet, Eli; Licht, Tamar
Abstract: Neurogenic roles of microglia (MG) are thought to include an active role in adult hippocampal neurogenesis in addition to their established roles in pruning surplus dendrites and clearing dead neuroblasts. However, identification of such a role and its delineation in the neurogenic cascade is yet to be established. Using diphtheria toxin‐aided MG ablation, we show that MG reduction in the DG—the site where neuronal stem cells (NSCs) reside—is sufficient to impede overall hippocampal neurogenesis due to reduced survival of newly formed neuroblasts. To examine whether MG residing in the hippocampal neurogenic zone are inherently different from MG residing elsewhere in the hippocampus, we compared growth factor responsiveness of DG MG with that of CA1 MG. Strikingly, transgenic induction of the potent neurogenic factor VEGF elicited robust on‐site MG expansion and activation exclusively in the DG and despite eliciting a comparable angiogenic response in the CA1 and elsewhere. Temporally, DG‐specific MG expansion preceded both angiogenic and neurogenic responses. Remarkably, even partial MG reduction during the process of VEGF‐induced neurogenesis led to reducing the number of newly formed neuroblasts to the basal level. Transcriptomic analysis of MG retrieved from the naïve DG and CA1 uncovered a set of genes preferentially expressed in DG MG. Notably the tyrosine kinase Axl is exclusively expressed in naïve and VEGF‐induced DG MG and its inhibition prevented neurogenesis augmentation by VEGF. Taken together, findings uncover inherent unique properties of DG MG of supporting both basal‐ and VEGF‐induced adult hippocampal neurogenesis. Main Points: Dentate gyrus microglia are a unique subpopulation which support neuroblasts survival. Dentate gyrus microglia are characterized by a unique set of genes and by being selectively reactive in response to the angiogenic and neurogenic factor VEGF.